THE CONCEPT OF ADOLESCENT EDUCATION CURRICULUM FROM THE HADITH PERSPECTIVE - Ali, Agus; Asyrofi, Asyrofi; Makmun, Syukron; Rokhim, Abdur; Mustopa, Mustopa; Jauharudin, Jauharudin; Fayadh, Muhammad (Universitas Labuhanbatu, 2025)
Purpose –This study aims to investigate the concept of a youth education curriculum based on Islamic hadith literature. The study is based on the idea that curriculum design should be thoroughly understood by educators, particularly by institutional leaders who engage with teenagers.Methodology – This qualitative study employs a library research design combined with a descriptive method. The key sources of information are Sahih Bukhārī, Fathul Baari, and Umdatul Qaari. Secondary materials include Tarbiyatul Awlad and an educational resource on curriculum development. Data was obtained using triangulation and the term